Gender differences in investments and risk preferences - Stein Terje Holden; Mesfin Tilahun (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2022)
We analyze individual investment behavior among 822 young men and women that are members of 111 formal business groups in northern Ethiopia. We collected baseline data and investment data one year later combined with incentivized field experiments to obtain dis-aggregated risk preference data. We find that business women on average invest significantly less at individual level than business men but Cohen's d values for the gender difference are moderate in size. Women are found to have higher Constant Relative Risk Aversion coefficients, to be more loss averse, but also to be more optimistic in their expectations than men. Women were also poorer in non-land assets, came from more land-poor parents and had lower incomes. The gender differences in risk attitudes and baseline endowments could explain some of but not all of the gender differences in investments.
Keywords: C93; D90; 330; Gender difference; Individual investment; Risk preferences; Prospect theory; Cohen's d; Business groups; Northern Ethiopia